Activities of government bodies and socio-political organizations on the creation of territorial autonomy of the Siberian Tatars (1989–1997) - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The purpose of the study conducted by the author is to determine a number of ethnic, economic and political factors. Factors that required the elaboration of the idea of creating territorial autonomy of the Siberian Tatars in the north of the Omsk and south of the Tyumen regions of the Russian Federation as an alternative to the growth of separatist insistence. At the same time, special attention is paid to the study of the views and activities of representatives of government bodies, socio-political organizations and subjects of economic relations in Western Siberia. The author’s research is conducted using a wide range of sources: documents of authorities and public organizations, reference materials, printed publications of authorities and public organizations, published memoirs of participants in the movement for the revival of Siberian Tatars and data obtained during meetings with them, materials of journalistic investigations. In the course of the research, the author turned to the method of historicism, in which synchronistic, statistical and comparative historical methods are used. The results of the study are the recognition of the inexpediency of creating the territorial autonomy of the Siberian Tatars based on ethnic factors and its complexity in view of the economic and political situation prevailing in the Russian Federation in the 1990.